Work engagement as a moderator between knowledge management practices and employee well-being among academia in selected Malaysian private universities / Siti Murni Mat Khairi - Mat Khairi, Siti Murni (2020)
Factors that support well-being have been extensively studied in the field of organisational behaviour, and the validated antecedents include social support at work, a high-performance work system, work pressure, work-family conflict and workaholism. However, the well-being of employees is rarely approached from a knowledge management perspective. Empirical research on knowledge management (KM) effects on employee well-being are therefore still scarce. By applying the Conservation of Resources (COR) theory, the aim of this study is to examine the significant relationship between knowledge management practices (i.e. knowledge acquisition, knowledge sharing, knowledge creation, knowledge codification and knowledge retention) and employee well-being with moderating effects of work engagement. Hypotheses were then empirically tested with structural equation modelling (SEM) using partial least square analysis (PLS) of the survey data set of 198 responses collected from academia in selected private universities located in the central region of Malaysia. The study showed that employees who acquired and gained more resources (knowledge acquisition and knowledge creation) are likely to improve their valued resources, the employee well-being that is consistent with the COR theory. This study also demonstrated that knowledge sharing, knowledge codification and knowledge retention are not significantly related to the promotion of employee well-being. Moreover, the results have shown that highly engaged employees strengthen the relationship between knowledge codification and employee well-being. Interestingly, the interaction of work engagement is significant on the relationship between knowledge creation and employee well-being but at the conditions with low engaged employees. Although some negative relationships have been identified in some facets of knowledge management with employee well-being, the current study contributes to understanding that knowledge management can improve the well-being of academia. Several implications have been derived from findings which then provide new inputs and insight for both scholars and industry practitioners. Knowledge management does effect on ‘soft-human issues’, the employee well-being and findings enrich the moderating role played by work engagement as suggested by COR theory. Therefore, management of private universities are advised to cultivate an appropriate atmosphere of KM practices and paying greater attention on human relations outcome (employee well-being) by implementing knowledge management and well-being as part of organisation’s strategy and performance (i.e. KPI, well-being index). Work engagement should be managed the same way that knowledge management is managed and a balanced approach for the engaged and low engaged employees is also important for the organisation. Future research should be conducted to further examined the proposed study beyond higher education sector. Additionally, future research may consider a different factors or antecedents that may improve employee well-being such as to include knowledge types, knowledge hiding or employee commitment as contingency variables. Moreover, employee well-being is a very broad concept and future researchers should embark into additional outcomes of the well-being concept including health (physical well-being) and social well-being in various fields.